Globalization and social policy: The threat to equitable welfare - Bob Deacon (United Nations Research Institute for Social Development (UNRISD), 2000)
This paper argues that neoliberal globalization is presenting a challenge to welfare provisioning in the industrialized countries and to the prospects for equitable social development in developing and transition economies. This challenge flows partly from the unregulated nature of the emerging global economy and partly from intellectual currents dominant in the global discourse concerning social policy and social development. The paper contends that certain global conditions are undermining the prospects for the alternative: equitable public social provision in both developed and developing countries. These conditions include the World Bank's preference for a safety-net and privatizing strategy for welfare; the self-interest of international non-governmental organizations (NGOs) in providing basic education, health and livelihood services that might otherwise be provided by the state; and the World Trade Organization's (WTO's) push for an open global market in health services, education and social insurance. Yet these disturbing trends are taking place in parallel with an apparent shift in the politics of globalization from orthodox economic liberalism to global social concern. The paper begins by reviewing the challenges faced by countries seeking to secure the social welfare of citizens and residents in the context of globalization. In the North, globalization has set welfare states in competition with each other. Moreover, the different kinds of welfare state are differently challenged by globalization, and have responded differently. Anglo-Saxon countries, which have residualized and privatized welfare provision, are in tune with liberalizing globalization, but at the cost of equity. Workplace-based welfare systems of the former state socialist countries, and payroll tax-based 'Bismarkian' insurance systems common in many Western European countries, are proving vulnerable to global competitive pressures. The social democratic, citizenship-based welfare systems funded out of consumption and income taxes, found in the Nordic countries, have been surprisingly sustainable in the face of global competitive pressures due to political will to maintain them. In the South, globalization has generated indebtedness that has undermined the capacity of governments to secure education, health and social protection. It has threatened social and labour standards, segmented social policy within countries and created zones excluded from any of the benefits of globalization. Next the paper considers the current global social policy discourse within and between international organizations and aid agencies. The International Monetary Fund (IMF) has recently shown signs of taking the social dimensions of globalization more seriously, by beginning to consider whether some degree of equity within countries is beneficial to economic growth. The World Bank has articulated more clearly its 'individual risk management approach' to social protection in the context of globalization. The Organisation for Economic Cooperation and Development (OECD) has asserted that globalization may lead to the need for more, not less, social expenditure. While the International Labour Organization (ILO) has begun to show signs of making concessions to the Bank's views on privatizing some aspects of social security, it has also shown an interest in a new universalism emerging from bottom-up movements in several countries. The views of the WTO on the desirability of a global market in health and social service provision are assuming new prominence. International NGOs are now more clearly divided into those acting as substitutes for government, and those advocating greater government responsibility for welfare. Yet within this discordant global discourse can be discerned elements of a new politics of global social responsibility. Orthodox economic liberalism and inhumane structural adjustment appear to be giving way to concern in the World Bank and the IMF with the social consequences of globalization. International development assistance is increasingly focusing on social development. United Nations agencies are giving more attention to the negative social consequences of globalization. Among the shifts in policy thinking and concrete steps that are being taken, which could herald more socially responsible globalization, are moves to globalize social rights, indications that social policy issues are moving up the development agenda and steps to regulate the global economy. The paper looks at each of these in turn, and at the disagreements as to how to proceed with this new orientation. It examines the dangers of the North moralizing about global social rights without providing the resources to realize them in practice. It also discusses whether the initiative to establish a code of principles and best practice for social policy will enable these dangers to be overcome. The paper then questions whether the move to establish development targets, such as basic education for all by 2015, represents global social progress or the legitimation of residual social policy. The obstacles to progressive North-South social policy and social development dialogue are also examined. In terms of the moves to inject social concerns into the global economy, the paper reviews conflicts of interest surrounding the failed WTO conference in Seattle, the proliferation of codes of conduct for transnational corporations and the debate about raising global taxes to finance social programmes. The paper argues that despite the apparent shift from global neoliberalism to global social responsibility, four tendencies within the new global paradigm, if pursued, will undermine equitable social progress and development-at a time when the resources exist to fund such advances. These tendencies are: the World Bank's belief that governments should provide only minimal levels of social protection; the concern of the OECD's Development Assistance Committee (DAC) to focus funding on only basic education and healthcare; the self-interest of international NGOs in substituting for government provision of services; and the moves being made within the WTO to open the global market in private healthcare, education and social insurance. Within the context of minimal and basic-level-only state provision, the middle classes of developing and transition economies will be enticed to purchase private social security schemes, private secondary and tertiary education, and private hospital and medical care. The wider repercussions are predictable. We know that only services for the neediest will remain-and that services for the poor are poor services. We know that those developed countries without universal public health and education provision are not only more unequal than those that do, but also more unsafe and crime ridden. This is the prospect for all countries that buy into this new global social development paradigm. Some policy measures to counteract this trend and to re-establish the place of equity in the discourse and practice of global social policy and development are suggested in this paper, together with an assessment of global forces that might be sympathetic to them. It is concluded that a major problem is the fragmentation and functional separation of agencies (WTO, World Bank, IMF, ILO, WHO, UNDP, UNESCO, OECD, regional groupings), and conflict and competition within and between them for the right to determine the content and other aspects of global social policy. Whether the five-year review of the World Summit for Social Development (Geneva 2000) begins the process of establishing a responsible and accountable global system of governance in the social sphere will depend to a large extent on political support from the European Union. It will also hinge on progressive voices from the South speaking out for improvements in the structure of global governance-in the interests of the North and the South, and of equity within and between countries.
Keywords: 330